RELEVANSI KURIKULUM PENDIDIKAN AGAMA ISLAM TERHADAP PEMBENTUKAN AKHLAK MULIA PESERTA DIDIK - Cucu Komariah; Chintia Nabilah; Asep Nurshobah; Erihadiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is using a qualitative method. Data collection through literature studies using observation guidelines, interview guidelines and documentary recording, accompanied by research indicators. Then descriptive data analysis and analysis are carried out by following the steps of data reduction, data display to drawing conclusions. This research was conducted at SDN Permata Biru, Cinunuk, Bandung. Looking at the facts on the ground, the challenges in forming students' noble morals are increasingly complex, especially in the midst of globalization. The PAI curriculum in Indonesia has also undergone various changes and received criticism, whether the current PAI curriculum is really suitable for the formation of students' morals.